Hemodynamic simulation in the aortic arch under anemic, diabetic, and healthy blood flow conditions using computational fluid dynamics - Farzana Akter Tina; Hashnayne Ahmed; Hena Rani Biswas (PLoS ONE, 2026)
This study examines the hemodynamic impact of anemic, diabetic, and healthy blood conditions in the human aortic arch using computational modeling. Blood rheology was represented by the shear-thinning Carreau–Yasuda model, and simulations were carried out in a patient-inspired aortic geometry under pulsatile flow. Velocity fields, pressure gradients, and wall shear stress (WSS) distributions were quantified to assess how altered hematocrit and viscosity affect vascular loading. Anemic blood, characterized by low viscosity, showed smooth low-resistance flow with reduced WSS, potentially limiting endothelial stimulation and impairing perfusion. Diabetic blood exhibited elevated viscosity and hematocrit, producing higher flow resistance, increased WSS, and disturbed secondary flows, consistent with vascular stiffening and remodeling risk. Healthy cases maintained balanced hemodynamics within physiological ranges. These findings highlight the mechanistic links between blood rheology and vascular stress, offering non-invasive insights for risk stratification in hematological and metabolic disorders, and supporting the integration of CFD-based analysis into clinical decision-making.